Responsabilidade social e marketing social: dois estudos de caso - Nascimento, Fabiano Pucci do (2002)
The objective of this research was to identify and to determine the foremost elements present in the development of social responsibility actions and social marketing programs in industrial units of two enterprises, located in Curitiba: Bosch and Inepar. Aspects related to the social management under the Post-Industrial 80ciety paradigm, the social responsibility and the social marketing were analyzed on the theoretical-empirical basis. 8pecifically in the these last two subjects, its basis formation and concepts evolution were deeply analyzed, as well as the different interpretations, treatments, uses and motivations to accomplish social character programs. lhe method that characterizes this research is the study of two distinct cases. lhe data were obtained through bibliographical analysis, internai documents analysis and externai communications, advertisements and brochures, direct observation and by semi-structured interviews, with managers and personnel of the studied enterprises, involved in the organization and conduction of social practices. lhe analysis was realized in a descriptive-qualitative formo lhe collected data revealed the existence of consonance and dissonance between the social responsibility and social marketing practice, and the enterprises discourse. lhe study main objective was to amplify the understanding about the social responsibility and social marketing practiced by the private sector, having as a reference their players vision within present social and economical rationalities that establish a new relationship model between the 8tate, enterprises and civil society.